Corporate Governance Reform as Institutional Innovation: The Case of Japan - Yoshikawa, Toru; Tsui-Auch, Lai Si; McGuire, Jean (Organization Science, 2007)
To address the convergence-divergence debate in corporate governance, we conduct a multiple-case, multiple-level study to analyze the diffusion of governance innovation in Japan. We argue that Japanese systems of corporate governance neither fully converge to, nor completely diverge from, the Anglo-American model. Rather, Sony—the pioneer of corporate governance reforms—and its followers selectively adopted features from this model, decoupled them from the original context, and tailored them to fit to their own situations to generate governance innovation. However, we find that the spread of innovation across firms and institutional levels is far from linear and straightforward, and that other well-regarded firms raised strong opposition to the institutionalization of corporate governance reforms. Eventually, the Ministry of Justice revised the Commercial Code to legitimize different systems, which led to the emergence of diverse corporate governance practices. Based on the results of our study, we construct an analytical framework to examine innovation diffusion in light of conflicting institutional pressures for change and continuity. Our analysis adds complexity to the convergence-divergence debate by identifying the creation of hybrid corporate governance systems and the nonlinear evolution of such systems as a result of interactions across multiple levels. We show the various degrees of decoupling from the Anglo-American model and identify the antecedents. We then extend the conventional focus of innovation research on diffusion across firms to examine diffusion across institutional levels. We also contribute to institutional theory by offering insights into organizational field formation and the conceptualization of the state in shaping institutional change and continuity.